Change and stability in the structure of cultural beliefs - Keskintürk, Turgut. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This thesis presents a formal approach to analyze cultural beliefs, attitudes and opinions as networks of survey responses. In two substantive empirical studies, the thesis draws from network science, research on culture and cognition, and recent studies on public opinion to investigate the change and stability in the structure of cultural beliefs. I make use of two nationally representative surveys to construct belief networks and analyze their structural properties to adjudicate diverse cultural theories. In both chapters, my central argument is grounded on the following hypothesis: individuals have relatively stable and coherent belief systems around institutionalized fields, and these belief systems are dynamic in the earlier periods of life and become much more solidified with age, but remain relatively variable across cultural, social, and political contexts. This thesis shows that opinions are organized with underlying, though diverse, logics in the population.
Keywords: Belief and doubt.; Cultural policy.; Material culture -- Religious aspects.